Helicopter Emergency Medical Service in the Republic of Croatia - Vidović, Andrija; Steiner, Sanja (Promet - Traffic&Transportation, 2007)
Current situation of emergency medical assistance indicatesthe need to organize faster and more efficient system oflinking all the parts of the Republic of Croatia. The solutioncan be found in the implementation of aviation as the fastestand therefore the best method of transporting the injured, diseasedand other persons who need urgent transpmt. The use ofmilitary helicopters for the purposes of emergency aviation doesnot satisfy the needs of the Republic of Croatia from the organizationaland legal aspect. There were 597 fatalities on the Croatianroads in 2005 and with the establishment of emergencyhelicopter medical service, the number of fatalities may be reducedby one third.